Effect of Power Amplifier Distortion on the Speech Transmission Index for Public Address Systems - DZIECHCIŃSKI, Paweł (Archives of Acoustics, 2022)
The effect of the power amplifier on speech intelligibility in public address systems is often marginalised – i.e. it is assumed that it does not introduce significant signal distortion. This approach is justified when the linear range of the amplifier is used. The large crest factor of the speech signal and economic considerations mean that the amplifier also works in the non-linear range. In this paper, the effect of power amplifier distortion on the speech transmission index for public address systems (STIPA) is presented. In the first step, this influence was evaluated by measurements for Class AB and D amplifiers. Then, a computer model of the public address system based on the direct STIPA method, taking into account the non-linear properties of the amplifier, was proposed. Using the computer model, the optimum amplifier driving values were determined taking into account the reverberation time and interfering noise.